Some notes on legitimate defense - Bouroncle Velásquez, Mauricio (2021)
The main basis of self-defense is the fact that the law can not conceive how unfair under any circumstances, and it is totally unfair that a person can not defend their own rights or those of another when they are being violated by a criminal. The basis of this idea all-important are two:. "Self-defense and the principle of maintaining the legal order" "The principle of individual protection" or Referring to the first defense of the legal rights themselves, it should also be mentioned that in this case the relationship between the legally protected interest and the injured is no importance, since only matter unlawful aggression. Hence when someone is unlawfully attacked, not required to defeat the defending legitimately clear that only certain cases